Primary health care engagement among marginalized people who use drugs in Ottawa, Canada - Donelle, Jessy; Bayoumi, Ahmed; Boucher, Lisa; Martin, Alana; Pineau, Dave; Diliso, Nicola; Renaud, Brad; Boyd, Rob; Oickle, Pam; Marshall, Zack; LeBlanc, Sean; Tyndall, Mark; et al. (International Journal of Population Data Science, 2018)
Introduction Engagement in primary health care may be lower among marginalized people who use drugs (PWUD) compared to the general population, despite having greater mental and physical healthcare needs as evidenced by higher co-morbidity, and more frequent use of emergency department care. Objectives and Approach We investigated which socio-structural factors were related to primary care engagement among PWUD using rich survey data from the Participatory Research in Ottawa: Understanding Drugs cohort study; these data were deterministically linked to several robust provincial-level health administrative databases held at the Institute for Clinical Evaluative Sciences. We defined primary care engagement over the 2 years prior to survey completion (March-December 2013) as: not engaged (<3 outpatient visits to the same family physician) versus engaged in care (3+ outpatient visits to the same family physician). Multi-variable logistic regression was used to identify factors associated with primary health care engagement. Results Among 663 participants, characteristics include: mean age of 41.4 years, 75.6% male, 66.7% in the lowest two income quintiles, and 51.1% with 6+ co-morbidities. 372 (56%) were engaged in primary care, with a mean of 15.97 visits per year (SD=20.18). Engagement was significantly associated with the following factors: receiving drug benefits from either the Ontario Disability Support Program (adjusted odds ratio [AOR] 4.48; 95% confidence interval [95%CI] 2.64 to 7.60) or Ontario Works (AOR 3.41; 95%CI 1.96 to 5.91), having ever taken methadone (AOR 3.05; 95%CI 1.92 to 4.87), mental health co-morbidity (AOR 2.93; 95%CI 1.97 to 4.36), engaging in sex work in the last 12 months (AOR 2.05; 95%CI 1.01 to 4.13), and having stable housing (AOR 1.98; 95%CI 1.30 to 3.01). Conclusion/Implications Nearly half of PWUD are not engaged in primary care, representing missed opportunities to improve health. Engagement in primary care may reflect both an increased need for health care, such as mental health disability, and increased access to primary care through other health and social services, such as housing support.